From Oil to Cities : Nigeria's Next Transformation - World Bank Group (World Bank, Washington, DC, 2016)
The Nigeria Urbanization Review serves the critical and timely purpose of understanding the challenges and opportunities of urbanization in Nigeria. The country’s rapid urban population growth and expansion is examined in relation to the account of its recent urban economic growth in order to seek for ways to finance urban development, particularly the provision of urban public goods and services. The objective of this analytical program is to provide diagnostic tools to inform policy dialogue and investment priorities on urbanization.